Promotion and Branding Strategy for Traditional Culinary Tourism in Cirebon City - Mustafa, Iva Yulia; Hernawati, Yuke (Jurnal Toursci, 2025)
Background. Cirebon is one of the cities in Indonesia that has a wealth of distinctive culinary, such as empal gentong, nasi jamblang, and tofu gejrot. Cirebon culinary is increasingly sought after by tourists in addition to Batik, cultural tourism, religious tourism, and others. With that, there needs to be a proper promotion and branding strategy so that Cirebon culinary can become better known and more competitive. The promotion and branding of traditional culinary tourism in Cirebon City is a strategic effort to enhance the attractiveness and quality of culinary destinations. Cirebon, known for its distinctive culinary offerings, has strong potential to attract both local and foreign tourists. Aims. This study aims to analyze the branding and promotional strategies used to develop culinary tourism in Cirebon City and to evaluate their impact on tourist interest. Methods. The research method used in this study is a mixed-methods approach. This method combines qualitative and quantitative methods. Result. The results of the study show that Cirebon culinary tourism branding still needs to be strengthened through product differentiation, the use of digital media, and collaboration between the government, business actors, and local communities. Promotional strategies based on digital marketing and culinary events have proven to be effective in increasing tourist attractions. Conclusion. The conclusion of this study confirms that strengthening brand identity and innovation in promotional strategies can be a key factor in increasing tourist visits to Cirebon City.